The influence of US dollar funding conditions on Asian financial markets. - Lee, Junkyu
It is observed that a depreciation of the domestic currency against the US dollar leads to a widening of the sovereign bond spread. This finding suggests a significant relationship between US dollar funding exposure, US dollar liquidity conditions, and domestic financial conditions in some emerging Asian economies. Yet, given that the magnitude of the effects varies across economies, the paper notes that policy prescriptions must be tailored individually.